Proceedings of the International Conference on Trends of Technologies and Innovations in Economic and Social Studies 2017 2017
DOI: 10.2991/ttiess-17.2017.90
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Articles of Fixed Assets Renewal of Russian Business Enterprises

Abstract: In the present article, the topicality of the chosen research theme is given proof. The need of the analysis of articles of fixed assets renewal of Russian business enterprises conditions not only a high level of competitive ability and effectiveness of activity, but also makes it possible to decrease process cost. Further, within the scope of the research, some problem aspects of articles of fixed assets renewal of the business enterprises resisting renewal of capital assets, are considered. On the ground of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Develop an algorithm for improving methods and forms of investment in innovation, taking into consideration the expansion of opportunities for attracting private and foreign capital, which use will allow leasing to be fully applied through the use of resources of Interstate Finance and Credit Institute, as a result of an increase in the volume of leasing transactions in countries (EAEU, BRICS, CIS) being most attractive when applying the leasing form of financing carried out on a returnable basis [5]. This scheme tracks step-by-step action of investment forms, where: the conclusion of a credit agreement by a leasing company with one of the interstate financial and credit institutions for the acquisition of leasing property; conclusion of a purchase-and-sale agreement by a leasing company with a supplier of leasing property for the purchase of leasing property; conclusion of an agreement with a service company for servicing the supplied leasing property to the leaseholder for the period of a leasing agreement; conclusion of an insurance agreement by a leasing company with an insurance company for the period of operation of leasing property; conclusion of an international leaseback agreement with the leaseholder of A country for the supply of leasing property subject to the terms of DDP delivery; conclusion of an agreement on the acquisition of a leasing contract of a leasing company with an investment company; delivery of leasing property to the leaseholder under an international return leasing agreement on DDP conditions; the sale of a leasing contract by the leasing company to an investment company with the transfer of funds to the lessor; return of funds received for the purchase of leasing property; transfer of leasing payments by the leaseholder of A country to an investment company under an international leaseback agreement; maintenance of leasing property by the service company under an international leaseback agreement; return of leasing property by the leaseholder of A country under the international return agreement of a leasing company with the subsequent modernization of the supplier's production facilities; conclusion of a credit agreement by a leasing company with a credit institution with modernization conditions for secondary transfer to leasing; conclusion of a contract for acquisition and modernization of leasing property for secondary transfer to leasing by a leasing company with a supplier of leasing property; conclusion of an agreement with a service company for maintenance of upgraded leasing property; conclusion of an insurance contract with an insurance company by a leasing company; conclusion of an international financial leasing contract by a leasing company with a leaseholder of B country for the supply of upgraded leasing property; conclusion of an agreement on the acquisition of a leasing contract with an investment company by a leasing company; delivery of leasing property to a leaseholder under an international financial leasing agreement on DDP conditions; sale of a leasing contract by the leasing company to an investment company with the transfer of funds to the lessor; return of funds received for the purchase of leasing property; transfer of leasing payments to an investment company by the leaseholder of B country under an international financial leasing agreement; maintenance of leasing property by the service company under an international financial leasing contract [6].…”
Section: Research Questionsmentioning
confidence: 99%
“…Develop an algorithm for improving methods and forms of investment in innovation, taking into consideration the expansion of opportunities for attracting private and foreign capital, which use will allow leasing to be fully applied through the use of resources of Interstate Finance and Credit Institute, as a result of an increase in the volume of leasing transactions in countries (EAEU, BRICS, CIS) being most attractive when applying the leasing form of financing carried out on a returnable basis [5]. This scheme tracks step-by-step action of investment forms, where: the conclusion of a credit agreement by a leasing company with one of the interstate financial and credit institutions for the acquisition of leasing property; conclusion of a purchase-and-sale agreement by a leasing company with a supplier of leasing property for the purchase of leasing property; conclusion of an agreement with a service company for servicing the supplied leasing property to the leaseholder for the period of a leasing agreement; conclusion of an insurance agreement by a leasing company with an insurance company for the period of operation of leasing property; conclusion of an international leaseback agreement with the leaseholder of A country for the supply of leasing property subject to the terms of DDP delivery; conclusion of an agreement on the acquisition of a leasing contract of a leasing company with an investment company; delivery of leasing property to the leaseholder under an international return leasing agreement on DDP conditions; the sale of a leasing contract by the leasing company to an investment company with the transfer of funds to the lessor; return of funds received for the purchase of leasing property; transfer of leasing payments by the leaseholder of A country to an investment company under an international leaseback agreement; maintenance of leasing property by the service company under an international leaseback agreement; return of leasing property by the leaseholder of A country under the international return agreement of a leasing company with the subsequent modernization of the supplier's production facilities; conclusion of a credit agreement by a leasing company with a credit institution with modernization conditions for secondary transfer to leasing; conclusion of a contract for acquisition and modernization of leasing property for secondary transfer to leasing by a leasing company with a supplier of leasing property; conclusion of an agreement with a service company for maintenance of upgraded leasing property; conclusion of an insurance contract with an insurance company by a leasing company; conclusion of an international financial leasing contract by a leasing company with a leaseholder of B country for the supply of upgraded leasing property; conclusion of an agreement on the acquisition of a leasing contract with an investment company by a leasing company; delivery of leasing property to a leaseholder under an international financial leasing agreement on DDP conditions; sale of a leasing contract by the leasing company to an investment company with the transfer of funds to the lessor; return of funds received for the purchase of leasing property; transfer of leasing payments to an investment company by the leaseholder of B country under an international financial leasing agreement; maintenance of leasing property by the service company under an international financial leasing contract [6].…”
Section: Research Questionsmentioning
confidence: 99%
“…The highest production efficiency and IA is based on finding and establishing reserves to improve the above criteria. [7] At every stage of the company's activities, the data need systematic evaluation on the basis of an integral indicator The content of the analyzed methodological approach consists in calculating the performance indicators of the R & D stages, introduction and performance. It turns out that the presented method is scientifically proven and allows: 1) to study the organization IA for specific time intervals;…”
Section: Research Questionsmentioning
confidence: 99%
“…At Thus, elimination of innovation financing restrictions and identification of optimum investment areas for innovation active enterprises are crucial research issues. The analysis showed that areas of innovation financing mechanism improvement are underexplored in existing research works (Nechaev, 2017).…”
Section: Public Financial Support For Innovation Activitiesmentioning
confidence: 99%